ANALYZING THE EFFECT OF CONSUMPTION VALUES ON CUSTOMER PURCHASE OF VIRTUAL GOODS IN DOTA 2: A CASE AT FEB UNSRAT MANADO - Djamaluddin, Reza .; Kindangen, Paulus .; Tielung, Maria . (Universitas Sam Ratulangi, 2017)
investigate what consumption values that could have effect usersâ€™ purchase decision on Dota 2 virtual goods in Manado with specific case at the Faculty of Economics and Business Unsrat. A quantitative method was applied to analyse data collected using purposive sampling. Multiple linear regression was employed to analyse the purchase decision model, Ftest and ttest were used to analyse simultaneous and partial effects of consumption values on purchase decision of virtual goods in Dota 2, respectively. It was revealed from this research that simultaneously effect of Functional Value, Social Value, Emotional Value, Satisfaction with The Game and Character Identification was significant on purchase decision of virtual goods in Dota 2, but partially this effect was only significant for values of Satisfaction With The Game and Character Identification. Online game industry of Dota 2 has to maintain and develop their virtual goods related to consumption values used in this research with special attention to items that related to the increase of satisfaction with the game and character identification. The future research may be focused on others indicators of consumption values that did not involve in this research.Keywords: consumption values, dota 2, purchase decision, virtual goodÂ